PENGARUH REWARD TERHADAP MINAT BELAJAR ANAK DIDIK KELAS VI SEKOLAH DASAR NEGERI 2 SIDODADI KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN TAHUN PELAJARAN 2022/2023 - Irvan Havidhu Wafa; Santika, Ana; Juhainah (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This study aims to find out the effect of rewards on the learning interest of grade VI students of State Elementary School 2 Sidodadi, Jati Agung District, South Lampung Regency for the 2022/2023 Academic Year. With the data collection technique using a questionnaire. The form of questionnaire that the researcher will use is a multiple-choice questionnaire with 4 alternative answers. The data that has been collected through a questionnaire, then the author processes it quantitatively, namely by determining the answer score from the statements that have been answered by the respondents. The results of the study showed that there was an effect of reward giving on the learning interest of Class VI students of Negri 2 Sidodadi Elementary School, the influence obtained was 21.0%. The effect of rewards on learning interest in Class VI students of Negri 2 Sidodadi Elementary School is also evident from the results of hypothesis testing using the t-t test formula with program calculations SPSS 26 obtained t calculation of 2.958 by using the singnifikan limit a = 0.05, then the table was obtained of 1.689, so it is known that the tcount ≥ ttable, (2.958 > 1.689) obtained the result of the Asymp value of 0.006 where the value is smaller than the probability of 0.05 (0.006 < 0.05). This means that the provision of rewards has a significant effect on interest in learning. Thus, Ho stated that there was no significant positive relationship between the provision of rewards and the students’ interest in learning was rejected, and on the contrary, Ha stated that there was a significant positive relationship between the provision of rewards and the students’ interest in learning was accepted.